The Role of Empathy in Reducing Prejudice: A Cross-Cultural Study in Diverse Elementary School Settings - Budiawan Budiawan; Vicheka Rith; Chenda Dara (Research Psychologie, Orientation et Conseil, 2025)
Prejudice is a pervasive issue in diverse societies, and addressing it at an early age can help reduce its long-term impact. This study explores the role of empathy in reducing prejudice among elementary school students in diverse cultural settings. The research aims to examine whether empathy training can effectively decrease prejudicial attitudes in students from different cultural backgrounds and whether such interventions are equally impactful across various cultural contexts. A mixed-methods design was employed, combining pre- and post-intervention surveys with in-depth interviews in a sample of 300 students from three culturally diverse elementary schools. The quantitative data, analyzed using paired t-tests and ANOVA, revealed a significant reduction in prejudicial attitudes among students who participated in empathy-building activities. The qualitative findings, derived from interviews with teachers and students, supported these results, suggesting that empathy training fostered greater understanding and respect for diversity. The study concludes that empathy plays a crucial role in reducing prejudice in young children and that culturally tailored empathy interventions are effective in diverse elementary school environments. This research emphasizes the importance of early interventions in promoting inclusivity and tolerance, offering practical insights for educators and policymakers in multicultural education.